Teacher Efforts To Improve Science Process Skills: Observation, Classification, and Data Table Making - Yahya, Gita Salsabilla Nurma; Darmaji, Darmaji; Kurniawan, Dwi Agus (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to systematically identify, analyze, and synthesize various teacher strategies used in science learning to develop students' Science Process Skills (SPS). The study focuses on developing indicators for observation, classification, and data tabulation as basic and integrated scientific skills. Methodology: This study employed a Systematic Literature Review (SLR) method, adhering to the PRISMA 2020 guidelines. The unit of analysis was scientific articles, not human participants. Thirty articles meeting the inclusion and exclusion criteria were selected through identification, screening, and eligibility assessment. They were then analyzed using document analysis and thematic synthesis. Main Findings: The study results indicate that active, experiential, and inquiry-oriented learning strategies, such as Guided Inquiry, Experimentation, and Project-Based Learning (PjBL), have proven effective in improving basic Science Process Skills, particularly the observation and classification indicators. However, this systematic review also revealed significant strategic weaknesses in the data table creation indicator. These weaknesses are caused by teachers' limitations in designing learning activities that explicitly involve data processing, visualization, and representation as the basis for students' scientific argumentation. Novelty/Originality of this study: The novelty of this research lies in the systematic mapping of the development gaps in data table creation indicators in science learning practices. This study provides a conceptual contribution by confirming that strengthening data processing and representation skills is a crucial component that bridges basic Science Process Skills to more complex and meaningful integrated science process skills.